Simulation of the Single Uphill and Osmotic Diffusion - Dung, Vu Ba (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: Uphill diffusion is a process of mass transmission in which the diffusion flux goes up to high concentration region and the mass flux of osmotic diffusion is not vanishing, when concentration gradient is equal to zero. Most of the uphill and osmotic diffusion takes place in multicomponent systems and the cause of uphill diffusion is the diffusion flux of any species is coupled with that of its partner species. In this paper, the uphill and osmotic diffusion in single component systems (single uphill and osmotic diffusion) are presented and simulated. Results showed that: i) The uphill and osmotic diffusion can take place for single component systems; ii) the cause of single uphill and osmotic diffusion is thermal velocity of molecules in low concentration region is greater than that in high concentration region; iii) simulated results agree with the theory.  Keywords: Single uphill and osmotic for single component systems.